Criminal Sanctions for Online Gambling Offenders - Ryo Martin Sopian; Erlina B; Zulfi Diane Zaini (LAWYER: Jurnal Hukum, 2024)
The advancement of digital technology has significantly impacted various forms of crime, including increasingly complex online gambling facilitated through trading and investment platforms. The case of Doni Salmanan, who promoted the Quotex platform via social media, resulting in victim losses of IDR 24.3 billion, illustrates how binary option trading platforms can be misused as covert gambling tools in the digital era. This study examines two primary issues: the factors driving offenders to engage in online gambling crimes and the judicial considerations in imposing criminal sanctions, based on Court Decision No. 576/Pid.Sus/2022/PN Blb. Understanding these issues is crucial for analyzing the role of law enforcement in addressing online gambling cases disguised as investments. This research employs normative and empirical juridical approaches, utilizing literature reviews and interviews with district and high court judges. A qualitative juridical analysis was conducted on relevant regulations, particularly Law No. 11 of 2008 on Electronic Information and Transactions. The findings indicate that offenders are motivated by easy internet access and profit opportunities as affiliates, exacerbated by weak regulation of binary option platforms. The court sentenced the defendant to four years in prison and fined IDR 1 billion for disseminating false information harmful to consumers but did not classify Quotex as an online gambling platform due to the absence of clear regulations. The study recommends strengthening regulations for binary option platforms, enhancing inter-agency coordination in law enforcement, and educating the public on the risks of illegal investments as potential gambling channels.